TINDAK PIDANA ILLEGAL LOGGING KETERKAITAN APARAT DALAM PENEGAKAN KEBIJAKAN HUKUM PIDANA: (Studi Kasus di Kabupaten Blora, Provinsi Jawa Tenggah) - Wirasaputri, Nina Mirantie (Fakultas Hukum Universitas Bangka Belitung, 2019)
Criminal sanctions cumulatively , impact / consequences of criminal acts in the field of Forestry is detrimental to the country's financial , economic and social sanctions it should not only a criminal sanctions to perpetrators with penalties as severe as a loss , but also must be considered a country with sanctions